School Strategies in Recording Student Discipline Violations through the TPD App - Mahanani, Sari; Suparman; Saputra, Wahyu Nanda Eka (Jurnal Praktik Baik Pembelajaran Sekolah dan Pesantren, 2025)
This study seeks to identify the types of disciplinary violations committed by students, explore how the TPD App facilitates the documentation of such violations, and examine strategies that can be implemented to minimize these infractions. Employing a descriptive qualitative research design, the study was conducted at Unggulan Aisyiyah Junior High School, a private institution located in Yogyakarta. Data were collected through a combination of observation, documentation, and in-depth interviews involving guidance and counseling teachers, the school principal, and a review of relevant institutional documents. The findings reveal two key insights. First, this application significantly enhances the process of recording student disciplinary violations, with a total of 561 infractions documented across 33 categories. Second, some of these violations may be mitigated through the provision of more intensive student support services—specifically, through the implementation of effective and efficient classical guidance and counseling interventions. These findings underscore the importance of integrating digital tools with targeted counseling strategies to promote student discipline. It is anticipated that the results of this study will contribute to the body of knowledge on school discipline and serve as a foundation for future research in the field.